The unilateral determination of price in contracts of sale governed by the Consumer Protection Act 68 of 2008 - Nagel, C.J. (Christoffel Johannes), 1954- (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.